Proceedings of the 2021 DigitalFUTURES 2021
DOI: 10.1007/978-981-16-5983-6_4
|View full text |Cite
|
Sign up to set email alerts
|

Exploration on Machine Learning Layout Generation of Chinese Private Garden in Southern Yangtze

Abstract: Machine learning has been proved to be feasible and reasonable in architectural field by extensive researches recently, whereas its potential is far from being tapped. Previous studies show that the training of GAN by labelling can enable a computer to grasp interrelationship of spatial elements and logical relationship between spatial elements and boundary. This study set the learning object as layout of private gardens in southern Yangtze with higher complexity. Chinese scholars usually analyse private garde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 4 publications
0
9
0
Order By: Relevance
“…Previous research has shown that training a GAN with labeling allows the ML algorithm to learn the interrelationships of urban spatial elements (Liu et al, 2021). The DLS methods with GAN offer a new codesign possibility.…”
Section: A Labeling Methods For Urban Layout Tasks Utilizing Co-decis...mentioning
confidence: 99%
See 3 more Smart Citations
“…Previous research has shown that training a GAN with labeling allows the ML algorithm to learn the interrelationships of urban spatial elements (Liu et al, 2021). The DLS methods with GAN offer a new codesign possibility.…”
Section: A Labeling Methods For Urban Layout Tasks Utilizing Co-decis...mentioning
confidence: 99%
“…The architect inputs design decisions (labels) to meet the urban design task, and the GAN quickly generates urban design proposals based on the chosen labels. However, in the current DLS approach, most of the inputs to the GAN are existing physical conditions of the site, such as existing boundaries (Tian, 2020), entrances (Liu et al, 2021), and roadway networks (Shen et al, 2020). These DLS methods lack the subjective speculative labeling of architects as input, in addition, there is a need for a systematic and automated method to replace manual labeling.…”
Section: A Labeling Methods For Urban Layout Tasks Utilizing Co-decis...mentioning
confidence: 99%
See 2 more Smart Citations
“…In recent years, machine learning technology has made some progress in the field of building layout generation [2,4,5,7]. With more complex research objects and ever larger scales, some scholars begin to explore the possibility of combining machine learning with campus planning and layout design.…”
Section: Related Work In the Field Of Architectural Layoutmentioning
confidence: 99%